Assessing Vinblastine and Proline Contents in Catharanthus roseus Cultivated on Inceptisol under Water Stress - Susanto, Simbar Sulanjari; Utami, Sri Nuryani Hidayah; Hanudin, Eko (Universitas Jenderal Soedirman, 2026)
ABSTRACT. Catharanthus roseus, formerly known as ornamental plant, has now been explored for its potentials as medicinal herb. One of the secondary metabolites produced, namely vinblastine, has been widely used to treat some human cancers. In addition, as the relatively high tolerance to drought, the plant species could produce proline, which plays important role in maintaining cellular osmotic pressure in an adverse condition. This study aims to assess the profiles of vinblastine and proline in C. roseus cultivated on inceptisol under water stress in combination with the applications of Zwavelzure Ammonium (ZA) fertilizer and rice husk biochar (RHB). A Split Plot Design was employed involving three treatments, namely water stress as the main plot and the combination of ZA fertilizer and RHB as the subplot. Three levels of the respective treatment were applied, namely 0, 2 and 4 days without watering; 0; 1.19 and 2.38 g/polybag of ZA fertilizer; and 0, 100 and 200 g/polybag of RHB. The results showed that the highest vinblastine content of 2,516.46 µg/g was obtained in the combination of 4 days without watering, 1.19 g/polybag ZA fertilizer and 200 g/polybag RHB. Meanwhile, the highest proline content of 31.62 µmol/g was found in the applications of 4 days without watering, 2.38 g/polybag ZA fertilizer and 0 g/polybag RHB. The supporting agronomic parameters revealed the best responses in the applications of daily watering, 2.38 g/polybag ZA fertilizer and 200 g/polybag RHB. It can be concluded that the production of vinblastine increases with the higher levels of water stress, ZA fertilizer and RHB, while that of proline increases with only the higher water stress and RHB. ZA fertilizer and RHB applications are shown to increase soil fertility, while daily watering optimizes the growth of C. roseus. Key words: Catharanthus roseus, inceptisol, proline, vinblastine, water stress